2012
DOI: 10.1111/j.1464-410x.2012.11297.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epithelial–mesenchymal transition markers in renal cell carcinoma: impact on prognostic outcomes in patients undergoing radical nephrectomy

Abstract: What's known on the subject? and What does the study add?There have been few studies evaluating the prognostic value of epithelial‐mesenchymal transition markers in renal cell carcinoma (RCC); therefore, the significance of these markers in the prognosis of patients with RCC, particularly that in those with localized disease, remains largely unknown.Consideration of the expression levels of potential epithelial‐mesenchymal transition markers, particularly clusterin and Twist in addition to conventional prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…The prognostic role of β-Catenin expression in RCC is controversial. Krabbe et al [18] could identify an association between reduced β-Catenin-expression and worse RFS and CSS, whereas there are several studies showing no association between β-Catenin-expression and survival [26,28]. Furthermore, there are several studies suggesting a worse prognostic effect of high cytoplasmic β-Catenin expression and worse survival [15,21,22].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The prognostic role of β-Catenin expression in RCC is controversial. Krabbe et al [18] could identify an association between reduced β-Catenin-expression and worse RFS and CSS, whereas there are several studies showing no association between β-Catenin-expression and survival [26,28]. Furthermore, there are several studies suggesting a worse prognostic effect of high cytoplasmic β-Catenin expression and worse survival [15,21,22].…”
Section: Discussionmentioning
confidence: 97%
“…It could be shown that high β-Cateninexpression is associated with higher grading [15] and advanced stage, vascular invasion, and tumor necrosis [21]. However, other studies could not prove the correlation with adverse clinical and pathological parameters [18,26,28]. On a functional level, stabilization and thus high β-Catenin-expression promotes cell proliferation, migration, and invasion in RCC [19,20].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They evaluated the membranous immunoexpression of E-cadherin, the cytoplasmic immunoexpression of vimentin, and the nuclear immunoexpression of Snail, Slug, ZEB1, ZEB2 and Twist1. We performed a semiquantitative estimation based on the intensity and extent of stained cells for each case, as previously described [22,23]. The staining intensity was graded from 0 to 3 (0  =  no staining at all, 1  =  weak, 2  =  moderate, 3  = strong).…”
Section: Methodsmentioning
confidence: 99%